Impact of Universal Newborn Hearing Screening on cochlear implanted children in Ireland. (June 2020) - Gabriel, Melissa M.; Geyer, Lina; McHugh, Christine; Thapa, Jyoti; Glynn, Fergal; Walshe, Peter; Simoes-Franklin, Cristina; Viani, Laura
Abstract: Objectives: Cochlear Implant (CI) is an established treatment for severe to profound hearing loss (HL). Early diagnosis and intervention in HL are crucial in order to provide access to sound and increase the likelihood of spoken language development in pre-lingually deaf children. In April 2011, the Health Service Executive (HSE) implemented the Universal Newborn Hearing Screening (UNHS) in a phased regional basis in Ireland. This study aimed to investigate the general clinical pathway for UNHS referrals to the CI service and to evaluate the impact of earlier referrals via UNHS on functional outcomes in children. Methods: The first part of this study constituted a retrospective review of 100 children referred to the National Hearing Implant and Research Centre (NHIRC) via UNHS from November 2011 to December 2016. Implanted children referred via UNHS were categorised into three groups according to their medical status. Their clinical pathway to cochlear implantation was evaluated. Functional outcomes were investigated based on medical and developmental status, respectively. In the second part of this study, developmentally healthy implanted children referred post-UNHS were compared with medically healthy children referred pre-UNHS under the age of four, from January 2005 to June 2011. Current implant status of children, age at referral and functional outcomes were investigated. Results: Medically healthy children were referred to the NHIRC at an earlier age than the medically complex children (2.8 months vs 5.2 months, p < 0.01) and the children presenting with auditory neuropathy spectrum disorder (ANSD) (2.8 months vs 5.3 months, p < 0.01). On average they attended their first appointment and were implanted at a younger age than the ANSD group (6.1 months vs 10.1 months, p < 0.01; 16.3 months vs 29.4 months, p < 0.001, respectively). Developmentally healthy children had significantly better functional outcomes than children with developmental delays. Children referred via UNHS were referred and implanted at a younger age than those referred pre-UNHS. The former group achieved better Categories of Auditory Performance (CAP) and Speech Intelligibility Rating (SIR) scores 2 years post-implantation. Conclusion: UNHS in Ireland is an important platform for earlier diagnosis and management of congenital HL and our results show that early intervention has a positive impact on functional outcomes in children.